Pajanan Debu Terhirup dan Gangguan Fungsi Paru Pada Pekerja Industri Batu Kapur (Studi Di Desa Mrisi Kecamatan Tanggungharjo Kabupaten Grobogan) - Yulaekah, Siti; Adi, M. Sakundarno; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2007)
ABSTRACT Background: Exposed to low concentration of inhaled dust for a long time can cause respiratory tract disorders such as restriction, obstruction or mixed. Generally, organic and non organic dust exposure will effect on obstruction of respiratory tract, which is indicated by decreasing of FEV1/FVC. Workers of limestone industries have a high risk from inhaled dust deposition on their respiratory tract. Absorption of inhaled dust particles in the lung is occurred by respiration mechanism. Method : This research purpose was to analyze association between inhaled dust exposure and lung function disorder on workers in limestone industry (Study at Village of Mrisi, Sub District of Tanggungharjo) in Grobogan Regency. This research was an observational study using cross sectional approach for 60 samples. Sample was carried out by using a systematic probability sampling. Data were analyzed by using Chi Square test after controlling for gender, age, working years, smoking habit, exercise, nutrient status, awareness in using Personal Protective Equipment and time of exposure. Multivariate analysis was carried out by Logistic Regression test with the method of backward stepwise. Result : The result of this research showed that inhaled dust exposure significantly influences the occurrence of lung function disorder (p = 0.02 and Odds Ratio = 5.833 with 95%CI : 1.865 – 18.245). Probability of inhaled dust exposure factor toward lung function disorder whichw was assessed by Logistic Regression formula resulted in inhaled dust exposure over the Threshold Limit Value of 3 mg/m3 is 68.6 %. Most of respondents who were exposed to dust and have significant association with the occurrence of lung disorder have some characteristics namely female, normal nutrient status, and awareness in using Personal Protective Equipment. Conclusion : The recommendation of this research is expected to be an input for local government and Health Service in particular, in making guidelines of the programs related to harmful effects from the workplace to the workers health, as well as for the needs of workplace monitoring and occupational health surveillance. Therefore, to make the programs succeed, it needs occupational promotion. Key Words : Inhaled Dust Exposure, Lung Function Disorder, Workers, Limestone Industry